Hydroxy-γ-sanshool from Zanthoxylum bungeanum (prickly ash) induces apoptosis of human colorectal cancer cell by activating P53 and Caspase 8 - Zhaojun, Chen; Lulin, Tan; Xin, Feng; Abdel-nasser, Singab; Zunguo, Lei; Xiong, Liu (Frontiers in Nutrition, 2022)
Sanshools, long-chain polyunsaturated amides in Zanthoxylum bungeanum (prickly ash), have important bioactivity. The objective was to assess inhibitory effects and molecular mechanisms of sanshools isolated from supercritical fluid (SCF) extract on human colon adenocarcinoma cells (HCT-116) cultured in vitro. Cells were exposed to various concentrations (0, 50, 90, or 130 μM) of sanshools for 24 or 48 h, with assessment of apoptosis and cell cycle arrest as well as regulatory gene and protein expression associated with apoptosis and the cell cycle. Sanshools profoundly inhibited growth of HCT-116 cells, with hydroxy-γ-sanshool (HRS) being the optimal active component (IC50=88.01 μM) inhibiting cell proliferation and having no cytotoxic effect to normal cells (IC50=481.52 μM) by CCK-8 assay. In HCT-116 cells, HRS inhibited cell growth, induced morphological distortion, and arrested the cell cycle at G1 phase (50.31 ± 4.13% versus 72.16 ± 8.14% in Control and 130 μM HRS, respectively), and also caused programmed cell death in a dose-dependent manner. The percentage of apoptotic cells were remarkably increased after treated with HRS (6.2, 11.9, 19.8 and 30.7% for 0, 50, 90 and 130 μM, respectively). Moreover, in HCT-116 cells, HRS significantly inhibited mRNA and protein levels of Cyclin D1, CDK4, PCNA, and increased mRNA and protein levels of P21, P53, Fas, and Caspase 8. Furthermore, inhibitors of P53 and Caspase 8 proteins significantly mitigated the HRS-induced cell cycle arrest and apoptosis. In conclusion, our study provides evidence that HRS induced human colorectal cancer cell apoptosis by up-regulating P53 and Caspase 8.